Professionalizing Care at Petronella Hospital: Javanese Agency, Colonial Medicine, and Healthcare Work in Yogyakarta (1900–1940) - Fathoni, Rifa'i Shodiq; Safitri, Ilmiawati (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
This article traces the professionalization of indigenous medical staff at Petronella Hospital, Yogyakarta, between 1900 and 1940. Addressing the historical gap regarding non-elite health workers, this study examines how marginalized Javanese individuals negotiated colonial disciplines to achieve social mobility. Using a historical method framed by subaltern theory based on colonial archives, this research reveals that Petronella served as an engine of mobility. The institution transformed unskilled domestic workers into professionals (zuster and mantri). Through the decentralized “Yogyakarta System,” Petronella produced state-recognized nurses and conducted a radical gender experiment by training male midwives to address high rural maternal mortality. Ultimately, this professionalization demonstrates how subaltern indigenous agency adopted medical modernity without forfeiting cultural roots.